STAT3-Specific Single Domain Nanobody Inhibits Expansion of Pathogenic Th17 Responses and Suppresses Uveitis in Mice - Mbanefo, Evaristus C.; Yan, Ming; Kang, Minkyung; Alhakeem, Sahar A.; Jittayasothorn, Yingyos; Yu, Cheng-Rong; Parihar, Ashutosh; Singh, Sunanda; Egwuagu, Charles E. (Frontiers in Immunology, 2021)
STAT3 activates transcription of genes that regulate cell growth, differentiation, and survival of mammalian cells. Genetic deletion of Stat3 in T cells has been shown to abrogate Th17 differentiation, suggesting that STAT3 is a potential therapeutic target for Th17-mediated diseases. However, a major impediment to therapeutic targeting of intracellular proteins such as STAT3 is the lack of efficient methods for delivering STAT3 inhibitors into cells. In this study, we developed a novel antibody (SBT-100) comprised of the variable (V) region of a STAT3-specific heavy chain molecule and demonstrate that this 15 kDa STAT3-specific nanobody enters human and mouse cells, and induced suppression of STAT3 activation and lymphocyte proliferation in a concentration-dependent manner. To investigate whether SBT-100 would be effective in suppressing inflammation in vivo, we induced experimental autoimmune uveitis (EAU) in C57BL/6J mice by active immunization with peptide from the ocular autoantigen, interphotoreceptor retinoid binding protein (IRBP651-670). Analysis of the retina by fundoscopy, histological examination, or optical coherence tomography showed that treatment of the mice with SBT-100 suppressed uveitis by inhibiting expansion of pathogenic Th17 cells that mediate EAU. Electroretinographic (ERG) recordings of dark and light adapted a- and b-waves showed that SBT-100 treatment rescued mice from developing significant visual impairment observed in untreated EAU mice. Adoptive transfer of activated IRBP-specific T cells from untreated EAU mice induced EAU, while EAU was significantly attenuated in mice that received IRBP-specific T cells from SBT-100 treated mice. Taken together, these results demonstrate efficacy of SBT-100 in mice and suggests its therapeutic potential for human autoimmune diseases.